The analysis of the causal dependences in risk between the crude oil market and the markets representing other asset classes - Wleklińska, Dagna (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
With the increasing volatility of the financial instruments, particularly oil which is a strategic energy resource, there is a need to acquire the financial markets wider than ever range of the analyses. The concept of Granger causality in risk is one of the possible directions of analysis of the interdependence between the financial markets. The aim of this study is therefore to verify the presence of the causal relationships in risk between the future prices of oil and the markets representing other asset classes: stocks, bonds, currencies. The data used relate to the periods from January 2000 to January of 2015. The results of the analysis provide arguments for the existence of a causal link between the oil price and the quotations of ten-year Japanese bonds. In relation to the exchange rates the occurrence of the causal relationships in risk was found for these currencies, which were quoted in dollars.